Ethical dilemmas in narrative research: a review informed by Eastern wisdom traditions - K. C., Rejina; Dahal, Niroj (Frontiers in Research Metrics and Analytics, 2026)
Narrative research is intended to explore human experiences. However, there are ethical dilemmas that challenge researchers beyond formal protocols. This review examines 16 empirical studies (2014-2023) alongside insights from Eastern wisdom traditions, drawing on the experiences of three university faculty members who have employed narrative inquiry methodology in their graduate-level research to explore ethical dilemmas and shortcomings. This review identifies key recurring dilemmas in narrative research, including navigating informed consent, ensuring anonymity/confidentiality, managing power dynamics, mitigating emotional vulnerability, and respecting cultural sensitivity. The findings feature ethical integrity that relies on continuous reflexivity, relational ethics, and trust-building-principles reflected in Eastern concepts such as Dharma (i.e., righteous duties) and Karma (i.e., selfless actions). The study emphasizes the importance of context-sensitive ethical practices that prioritize participant dignity and the researcher's integrity. The article addresses the implications of creating ethical dilemmas in narrative research guidelines, provides ongoing ethical training, and promotes collaborative learning among researchers to enhance the trustworthiness of qualitative research in general and narrative research in particular.